Electron-ion mixed conductor solid electrolyte material and preparation method and application thereof
By combining the metal organic frame material with the sulfide solid electrolyte to form an electron-ion hybrid conductor solid electrolyte material, the problems of poor interface contact and large amount of auxiliary materials in sulfide-based all-solid-state batteries are solved, and higher battery performance and energy density are achieved.
Patent Information
- Application Number
- CN202411733800.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
AI Technical Summary
In a sulfide-based all-solid state battery, the solid-solid interface contact between the electrode and the electrolyte is poor, resulting in high interface resistance, affecting the battery's power output and cycling performance. At the same time, the addition of auxiliary materials reduces the utilization rate of the positive electrode active material and the energy density of the overall battery cell.
The metal organic frame material (MOF) is used to combine with the sulfide solid electrolyte to form an electron-ion hybrid conductor solid electrolyte material. It is uniformly stirred and rotated by alcohol solvents, and combined with low-temperature calcination, the structure and performance of the material are adjusted.
It reduces the interface contact loss between materials, reduces the internal resistance of the battery cell, improves the utilization rate of the positive electrode active substance and the energy density of the battery, and enhances the rate performance and cycle stability of the battery.
Smart Images

Figure BDA0005160982660000121 
Figure BDA0005160982660000131
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electrode materials, and in particular to an electron-ion mixed conductor solid electrolyte material and a preparation method and application thereof. Background Art
[0002] All-solid-state batteries represent the next generation of battery technology, solving the energy density and safety limitations of traditional lithium-ion batteries. Among them, sulfide-based all-solid-state batteries are an emerging battery technology. Due to their high ionic conductivity and good mechanical properties, they are considered to be the most commercially promising all-solid-state battery system. Sulfide-based all-solid-state batteries use sulfides as electrolytes. Compared with traditional liquid batteries, all-solid-state batteries have potential advantages in safety, energy density, and cycle life. However, sulfide-based all-solid-state battery systems currently still have some shortcomings and challenges. For example, the solid-solid interface contact between the electrodes and electrolytes in all-solid-state batteries is poor, resulting in higher interface resistance, which affects the power output and cycle performance of the battery. At the same time, interfacial chemical reactions may occur between the sulfide electrolyte and the electrode material to form an undesirable interface layer, which affects the stability and long-term performance of the battery.
[0003] At the same time, in the prior art, when preparing the positive electrode of the all-solid-state battery, in addition to the positive electrode active material, auxiliary materials such as ion-conducting materials, binders and conductive agents need to be added to ensure that the composite positive electrode maintains the positive electrode in a mixed ion-electron conductor state during charging and discharging. However, the addition of auxiliary materials will reduce the utilization rate of the positive electrode active material to a certain extent, and reduce the overall battery cell energy density; on the other hand, the introduction of new interfaces between auxiliary materials (such as between ion-conducting materials and conductive agents) will bring more interface reactions and further increase the internal resistance of the battery cell.
[0004] In order to solve the above-mentioned problems of interface reaction and internal resistance of the battery cell, it is crucial to select suitable framework materials to cooperate with sulfide electrolytes. Conductive metal organic framework (MOF) materials have advantages such as high conductivity, large specific surface area, abundant active sites and large pore structure. Compared with other traditional energy storage materials such as carbon materials and metal oxide materials, they have more structural advantages, especially in the field of electrochemical energy storage. In short, MOF materials have the advantages of abundant resources, strong structural design, good conductivity, and stable framework structure. If they can be applied to the positive electrode of all-solid-state batteries, they are expected to solve the above-mentioned problems. Summary of the invention
[0005] The purpose of the present application is to provide an electron-ion mixed conductor solid electrolyte material and a preparation method and application thereof. The electron-ion mixed solid electrolyte material is composed of a metal organic framework material (MOF) and a sulfide solid electrolyte present in the pores and voids of the MOF material. When used in an all-solid-state battery, it can reduce the polarization phenomenon of the battery cell, enhance the rate performance of the battery cell, improve the utilization rate of the positive electrode active material, and improve the energy density.
[0006] In a first aspect, the present application provides an electron-ion mixed conductor solid electrolyte material, characterized in that the electron-ion mixed conductor solid electrolyte material is composited with a metal organic framework material as a framework and embedded in a sulfide solid electrolyte, and the electronic conductivity of the metal organic framework material is greater than 10 -2 S / cm.
[0007] In the present invention, a sulfide solid electrolyte is used to prepare an electron-ion mixed conductor solid electrolyte material. The sulfide solid electrolyte has a higher ionic conductivity than oxides and polymer electrolytes. After being used in an all-solid-state battery, the power characteristics and temperature adaptability of the all-solid-state battery can be significantly improved. Moreover, since the solid electrolyte is non-flammable and non-volatile, it is safer than a traditional liquid lithium-ion battery.
[0008] Furthermore, the electrochemical stability and interface stability of sulfide solid electrolytes are poor. Therefore, the present invention adopts a metal organic framework material as a framework. The metal organic framework material has a highly ordered structure, high porosity and specific surface area, and its structure can be adjusted as needed, providing the possibility for the embedding of sulfide solid electrolytes.
[0009] Furthermore, in the present invention, the metal organic framework material is used as a carrier of the sulfide solid electrolyte, and is compounded with the sulfide solid electrolyte to form a mixed ion-electron structure, and is fully mixed with the positive electrode active material, which is beneficial to reduce the interface contact loss between the materials. Secondly, the metal organic framework material itself can provide sufficient electronic conductive channels, and the sulfide electrolyte therein can ensure that the ionic conductivity of the composite positive electrode is not affected. Therefore, the metal organic framework material can play the role of a conductive agent in the composite positive electrode, thereby reducing the amount of conductive agent in the composite positive electrode, and even eliminating the need for a conductive agent, thereby reducing the amount of auxiliary materials, reducing the polarization of the battery cell, and improving the utilization rate of the positive electrode active material.
[0010] Furthermore, in order to make the prepared electron-ion mixed conductor solid electrolyte material have suitable electronic conductivity, the electronic conductivity of the metal organic framework material is limited to greater than 10 -2S / cm, ensuring that ions have a suitable migration path and rate in the material during use and reducing the interface impedance, thereby improving the overall conductivity of the electron-ion mixed conductor solid electrolyte material.
[0011] In some embodiments, the mixing mass ratio of the metal organic framework material and the sulfide solid electrolyte is 1:2-1:20.
[0012] Sulfide solid electrolytes can provide a fast ion transport path at room temperature, and therefore generally have a higher ionic conductivity, and the interface contact between the metal organic framework material (MOF) and the sulfide solid electrolyte will affect charge transfer. When the metal organic framework material ratio is low, it will not significantly affect the ionic conductivity of the sulfide solid electrolyte, but an excessively high ratio of metal organic framework materials will reduce the available ion transport channels, resulting in a decrease in ionic conductivity. At the same time, the increase in the proportion of MOF will also increase the electronic conductivity of the overall composite material, but an excessively high ratio may cause the sulfide solid electrolyte matrix to be destroyed, thereby reducing electronic conductivity. Therefore, in the embodiment, it is necessary to control the mixed mass ratio of the metal organic framework material and the sulfide solid electrolyte to ensure that the prepared electronic-ion mixed conductor solid electrolyte material has both high electronic conductivity and ionic conductivity.
[0013] In some embodiments, the sulfide solid electrolyte includes at least Li 7-a PS 6-a X a (where X is a halogen element, 0≤a≤2), Li2S-P2S5, Li2S-P2S5-LIX (where X is a halogen element), Li2S-P2S5-Li2O, Li2S-P2S5-P2O5, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers, and Z is one of Ge, Zn or Ga), Li2S-SiS2-Li p MO q (wherein p and q are positive numbers, and M is one of P, Si, Ge, B, Al, Ga or In), one of Li2S-GeS2, Li2S-SiS2-Li3PO4.
[0014] The above-mentioned sulfide solid electrolyte selected by the present invention has a high lithium ion conductivity, which can effectively reduce the polarization phenomenon of the battery during the charging and discharging process, improve the power performance of the battery, and most sulfide solid electrolytes have low reactivity with lithium metal, which can inhibit the growth of lithium dendrites to a certain extent, thereby improving the safety performance of the battery. Furthermore, a good solid-solid interface can be formed between the sulfide solid electrolyte and the positive electrode material, which helps to reduce the interface resistance and improve the cycle stability of the entire battery. At the same time, many sulfide solid electrolytes have a wide electrochemical stability window, which is conducive to matching high-voltage positive electrode materials and improving the overall energy density of the battery.
[0015] In some embodiments, the metal organic framework material includes at least one of Cu-BHT, Co-BHT, Cu-HAB, Co-HAB, Cu-CAT, M2(TTFTB) (M is one of Mn, Co, Zn or Cd), ZnCo-ZIF, Cu-HHTQ, Cu-BTC, and Ni3(HITP)2.
[0016] In a second aspect, a method for preparing an electron-ion mixed conductor solid electrolyte material as described in any one of the first aspects is provided, characterized in that it comprises the following steps:
[0017] Step 1: Weigh the sulfide solid electrolyte and the metal organic framework material according to a proportion, add them into an alcohol solvent and stir them evenly to obtain material 1;
[0018] Step 2: subjecting material 1 to a rotary drying process to remove the alcohol solvent, thereby obtaining material 2;
[0019] Step 3: Calcinate material 2 to obtain an electron-ion mixed conductor solid electrolyte material.
[0020] The electron-ion mixed conductor solid electrolyte material of the present invention is equivalent to compounding the conductive agent and ion-conducting material in the traditional all-solid-state positive electrode. Since the metal organic framework material and the sulfide solid electrolyte material can be dissolved in alcohol solvents, the two materials can be mixed at the molecular level, which is beneficial to reduce the interface contact loss between the materials and reduce the internal resistance of the battery cell.
[0021] In some embodiments, in step 1, the alcohol solvent includes at least one of ethanol, methanol, isopropanol, benzyl alcohol, ethylene glycol, glycerol, butanol, and cyclohexanol.
[0022] In the embodiment, the above-mentioned alcohol solvent is used to dissolve the metal organic framework material and the sulfide solid electrolyte material and perform a composite operation, which can improve the dispersibility of the metal organic framework material and the sulfide solid electrolyte in the solution, reduce the agglomeration phenomenon, reduce the defects and holes in the sulfide solid electrolyte, thereby improving the mechanical strength and electrochemical stability of the electrolyte, and to a certain extent adjust the porosity and pore size of the metal organic framework material, help improve the uniformity of the sulfide solid electrolyte in the metal organic framework material, and help the sulfide solid electrolyte to form a microstructure that is more conducive to ion transmission in the pores of the metal organic framework material. Further, the hydroxyl group of the alcohol solvent can coordinate with the metal ion, thereby protecting the metal center from being hydrolyzed, maintaining the structural stability of the metal organic framework material, and thereby forming a composite structure of a uniform and stable electron-ion mixed conductor solid electrolyte material.
[0023] In some embodiments, in step 1, the stirring speed is 450-500 rpm, and the stirring time is 8-12 h.
[0024] In some embodiments, in step 3, the calcination temperature is 100-300° C., and the calcination time is 1-10 h.
[0025] Although a higher calcination temperature can improve the overall thermal stability of the composite material, it may also destroy the microporous structure of the metal organic framework material, resulting in pore collapse and the inability of the sulfide solid electrolyte to be evenly filled. At the same time, at higher temperatures, the grains of the sulfide solid electrolyte may grow, affecting its ionic conductivity. Therefore, in the embodiment, a low-temperature calcination method is adopted, and the calcination temperature is controlled to be 100-300°C. Within this range, the interface interaction between the metal organic framework material and the sulfide solid electrolyte can be enhanced, and the metal organic framework material can be controlled to undergo a phase change, from a metal organic framework structure to a more stable metal oxide structure, which is beneficial to improving the overall performance of the electron-ion mixed conductor solid electrolyte material.
[0026] In a third aspect, an all-solid-state battery is provided, characterized in that the all-solid-state battery includes a positive electrode layer, and the positive electrode layer includes the electron-ion conductor solid electrolyte material described in any one of the first aspect or the electron-ion mixed conductor solid electrolyte material prepared by the preparation method described in any one of the second aspect.
[0027] The beneficial effects of the electron-ion mixed conductor solid electrolyte material and the preparation method thereof provided by the present invention include but are not limited to the following:
[0028] (1) The electron-ion mixed conductor solid electrolyte material provided by the present invention utilizes a metal organic framework material as a carrier of a sulfide solid electrolyte, and forms a mixed ion-electron conductive structure by compounding with a sulfide solid electrolyte, and is fully mixed with the positive electrode active material, which is beneficial to reducing the interface contact loss between the materials. Secondly, the metal organic framework material itself can provide sufficient electronic conductive channels, and the sulfide electrolyte therein can ensure that the ionic conductivity of the composite positive electrode is not affected. Therefore, the metal organic framework material can play the role of a conductive agent in the composite positive electrode, thereby reducing the amount of conductive agent used in the composite positive electrode, and even eliminating the need for the presence of a conductive agent, thereby achieving the goal of reducing the amount of auxiliary materials used, reducing the polarization of the battery cell, and improving the utilization rate of the positive electrode active material.
[0029] (2) The present invention limits the electronic conductivity of the metal organic framework material to greater than 10 -2 S / cm, ensuring that ions have a suitable migration path and rate in the material during use and reducing the interface impedance, thereby improving the overall conductivity of the electron-ion mixed conductor solid electrolyte material.
[0030] (3) The electron-ion mixed conductor solid electrolyte material of the present invention is equivalent to combining the conductive agent and the ion-conducting material in the traditional all-solid-state positive electrode. Since the metal organic framework material and the sulfide solid electrolyte material can be dissolved in alcohol solvents, the two materials can be mixed at the molecular level, which is beneficial to reduce the interface contact loss between the materials and reduce the internal resistance of the battery cell.
[0031] (4) The preparation method of the electron-ion mixed conductor solid electrolyte material of the present invention enhances the interface interaction between the metal organic framework material and the sulfide solid electrolyte by controlling the calcination temperature, and controls the metal organic framework material to undergo a phase transition from a metal organic framework structure to a more stable metal oxide structure, which is beneficial to improving the overall performance of the electron-ion mixed conductor solid electrolyte material. DETAILED DESCRIPTION
[0032] The following description provides specific application scenarios and requirements of the present application, with the purpose of enabling those skilled in the art to make and use the content in the present application. It will be apparent to those skilled in the art that various local modifications to the disclosed embodiments are apparent, and the general principles defined herein may be applied to other embodiments and applications without departing from the spirit and scope of the present application. Therefore, the present application is not limited to the embodiments shown, but to the widest scope consistent with the claims.
[0033] The present application provides an electron-ion mixed conductor solid electrolyte material, characterized in that the electron-ion mixed conductor solid electrolyte material is composited by embedding a sulfide solid electrolyte into a metal organic framework material as a framework, and the electronic conductivity of the metal organic framework material is greater than 10 -2 S / cm, for example greater than 10 -1 S / cm, 10S / cm, 100S / cm or 1000S / cm.
[0034] In the present application, a metal organic framework material is used as a carrier of a sulfide solid electrolyte, which is compounded with a sulfide solid electrolyte to form a mixed ion-electron conductive structure and fully mixed with the positive electrode active material, which is beneficial to reducing the interface contact loss between materials. Secondly, the metal organic framework material itself can provide sufficient electronic conductive channels, and the sulfide electrolyte therein can ensure that the ionic conductivity of the composite positive electrode is not affected. Therefore, the metal organic framework material can play the role of a conductive agent in the composite positive electrode, thereby reducing the amount of conductive agent in the composite positive electrode, and even eliminating the need for the presence of a conductive agent, thereby reducing the amount of auxiliary materials, reducing the polarization of the battery cell, and improving the utilization rate of the positive electrode active material.
[0035] Furthermore, in order to make the prepared electron-ion mixed conductor solid electrolyte material have suitable electronic conductivity, the electronic conductivity of the metal organic framework material is limited to greater than 10 -2 S / cm, ensuring that ions have a suitable migration path and rate in the material during use and reducing the interface impedance, thereby improving the overall conductivity of the electron-ion mixed conductor solid electrolyte material.
[0036] The electron-ion mixed conductor solid electrolyte material provided in the present application and its preparation method and application will be described in detail below in conjunction with specific embodiments.
[0037] The present application provides an electron-ion mixed conductor solid electrolyte material, characterized in that the electron-ion mixed conductor solid electrolyte material is composited by embedding a sulfide solid electrolyte into a metal organic framework material as a framework, and the electronic conductivity of the metal organic framework material is greater than 10 -2 S / cm.
[0038] In some embodiments, the mixing mass ratio of the metal organic framework material and the sulfide solid electrolyte is 1:2-1:20, for example, 1:2, 1:5, 1:8, 1:11, 1:14, 1:17 or 1:20.
[0039] In some embodiments, the sulfide solid electrolyte includes at least Li 7-a PS 6-a X a(where X is a halogen element, 0≤a≤2), Li2S-P2S5, Li2S-P2S5-LIX (where X is a halogen element), Li2S-P2S5-Li2O, Li2S-P2S5-P2O5, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers, and Z is one of Ge, Zn or Ga), Li2S-SiS2-Li p MO q (wherein p and q are positive numbers, and M is one of P, Si, Ge, B, Al, Ga or In), one of Li2S-GeS2, Li2S-SiS2-Li3PO4.
[0040] In some embodiments, the metal organic framework material includes at least one of Cu-BHT, Co-BHT, Cu-HAB, Co-HAB, Cu-CAT, M2(TTFTB) (M is one of Mn, Co, Zn or Cd), ZnCo-ZIF, Cu-HHTQ, Cu-BTC, and Ni3(HITP)2.
[0041] The present application provides a method for preparing the electron-ion mixed conductor solid electrolyte material, characterized in that it comprises the following steps:
[0042] Step 1: Weigh the sulfide solid electrolyte and the metal organic framework material according to a proportion, add them into an alcohol solvent and stir them evenly to obtain material 1;
[0043] Step 2: subjecting material 1 to a rotary drying process to remove the alcohol solvent, thereby obtaining material 2;
[0044] Step 3: Calcinate material 2 to obtain an electron-ion mixed conductor solid electrolyte material.
[0045] In some embodiments, in step 1, the alcohol solvent includes at least one of ethanol, methanol, isopropanol, benzyl alcohol, ethylene glycol, glycerol, butanol, and cyclohexanol.
[0046] In some embodiments, in step 1, the stirring speed is 450-500 rpm, and the stirring time is 8-12 h.
[0047] In some embodiments, in step 3, the calcination temperature is 100-300°C, for example, 100°C, 150°C, 200°C, 250°C or 300°C, and the calcination time is 1-10h, for example, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h.
[0048] Example 1
[0049] This embodiment provides an electron-ion mixed conductor solid electrolyte material, which is composed of a MOF material and a sulfide electrolyte; wherein the sulfide solid electrolyte is a sulfide-silver-germanium mineral structure Li6PS5Cl, and the MOF material is Cu-BHT, and its electronic conductivity is 1580S / cm.
[0050] The specific preparation process of the sulfide solid electrolyte material of this embodiment is as follows:
[0051] S1. The sulfide electrolyte Li6PS5Cl and Cu-BHT were weighed in a mass ratio of 8:1 and put into an ethanol solvent with a solid content of 60%. The mixture was then magnetically stirred at a speed of 500 rpm for 12 h to ensure that the electrolyte and the MOF material were fully mixed to obtain material 1.
[0052] S2, subjecting material 1 to a rotary drying treatment to remove the alcohol solvent, thereby obtaining a Cu-BHT-Li6PS5Cl (material 2) dry powder;
[0053] S3. Calcine material 2 at 200° C. for 8 h to obtain an electron-ion mixed conductor solid electrolyte material.
[0054] Comparative Example 1
[0055] This comparative example provides an electron-ion mixed conductor solid electrolyte material, which is composed of a MOF material and a sulfide electrolyte; wherein the sulfide solid electrolyte is a sulfur silver germanium mineral structure Li6PS5Cl, and the MOF material is ZIF-8, whose electronic conductivity is less than 10 -6 S / cm.
[0056] The specific preparation process of the sulfide solid electrolyte material of this embodiment is as follows:
[0057] S1. The sulfide electrolyte Li6PS5Cl and ZIF-8 were weighed in a mass ratio of 8:1 and put into anhydrous ethanol solvent with a solid content of 60%. The mixture was then magnetically stirred at a speed of 500 rpm for 12 h to ensure that the electrolyte and the MOF material were fully mixed to obtain material 1.
[0058] S2, subjecting material 1 to a rotary drying treatment to remove the alcohol solvent, thereby obtaining a dry powder of ZIF-8-Li6PS5Cl (material 2);
[0059] S3. Calcine material 2 at 200° C. for 8 h to obtain an electron-ion mixed conductor solid electrolyte material.
[0060] The difference between Comparative Example 1 and Example 1 is that the MOF material used in Comparative Example 1 is ZIF-8, whose electronic conductivity is less than 10 -6 S / cm, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0061] Comparative Example 2
[0062] The embodiment provides an electron-ion mixed conductor solid electrolyte material, which is composed of a graphene material and a sulfide electrolyte; wherein the sulfide solid electrolyte is a sulfur-silver-germanium mineral structure Li6PS5Cl.
[0063] The specific preparation process of the sulfide solid electrolyte material of this embodiment is as follows:
[0064] S1. The sulfide electrolyte Li6PS5Cl and graphene were weighed in a mass ratio of 8:1 and put into an anhydrous ethanol solvent with a solid content of 60%. The mixture was then magnetically stirred at a speed of 500 rpm for 12 h to ensure that the electrolyte and graphene were fully mixed, thereby obtaining material 1.
[0065] S2, subjecting material 1 to a rotary drying process to remove alcohol solvents, thereby obtaining graphene-Li6PS5Cl (material 2) dry powder;
[0066] S3. Calcinate material 2 at 200° C. to obtain an electron-ion mixed conductor solid electrolyte material.
[0067] The difference between Comparative Example 2 and Example 1 is that the metal organic framework material is replaced by graphene material in Comparative Example 2, and other raw materials, amounts and preparation methods are the same as those in Example 1.
[0068] Example 2
[0069] This embodiment provides an electron-ion mixed conductor solid electrolyte material, in which the MOF material is replaced with Ni3(HITP)2 (whose electronic conductivity is 4000 S / cm), and the remaining steps are the same as those in Embodiment 1.
[0070] Example 3
[0071] This embodiment provides an electron-ion mixed conductor solid electrolyte material, in which the sulfide solid electrolyte material replaces Li2S-P2S5-P2O5, and the remaining steps are the same as those in Embodiment 1.
[0072] Example 4
[0073] This embodiment provides an electron-ion mixed conductor solid electrolyte material, in which the mass ratio of sulfide solid electrolyte to MOF is replaced with 5:1, and the remaining steps are the same as those in Embodiment 1.
[0074] Example 5
[0075] This embodiment provides an electron-ion mixed conductor solid electrolyte material. The calcination temperature in step 3 is adjusted to 150° C., and the remaining steps are the same as those in embodiment 1.
[0076] Example 6
[0077] This embodiment provides an electron-ion mixed conductor solid electrolyte material, the solvent in S1 is adjusted to isopropanol, and the remaining steps are the same as those in Embodiment 1.
[0078] Example 7
[0079] This embodiment provides an electron-ion mixed conductor solid electrolyte material, in which the MOF material is replaced with Co-HAB (whose electronic conductivity is 1.57 S / cm), and the remaining steps are the same as those in Embodiment 1.
[0080] Example 8
[0081] This embodiment provides an electron-ion mixed conductor solid electrolyte material. The sintering temperature in S3 is adjusted to 300° C., the sintering time is adjusted to 2 h, and the remaining steps are the same as those in Embodiment 1.
[0082] Performance Testing
[0083] 1. Test samples:
[0084] 2.2 Ionic conductivity test:
[0085] Each sample was pressed into a sheet-like sulfide solid electrolyte material with a diameter of 10 mm and a thickness of 1 mm under the conditions of a water content of less than 10 ppm and a pressure of 200 MPa. Then, an electrochemical impedance spectroscopy (EIS) test was performed at room temperature of 25°C with carbon as the blocking electrode to calculate the ionic conductivity.
[0086] 2.3 Electronic conductivity test:
[0087] The sample for measuring ionic conductivity was used for electronic conductivity test, and the test method was DC polarization method. The DC polarization voltage was 1.0V, the application time was 1800s, and the DC polarization test was carried out at room temperature 25°C. The polarization voltage was read and the electronic conductivity was calculated.
[0088] 2.4 Cycle test of all-solid-state batteries:
[0089] The assembly method of the all-solid-state battery is as follows: positive electrode NCM811, surface loading 4mAh / cm 2 The negative electrode is nano-silicon, the active material content in the positive electrode is 75wt%, the electrolyte adopts the sulfide solid electrolyte material prepared in each embodiment and comparative example, the content is 23wt%, the binder content is 1%, the conductive agent content is 1%, the electrolyte layer thickness is 100μm, and the electrolyte material is a single component Li6PS5Cl.
[0090] The cycle test method is as follows: the charge and discharge voltage is 3.0-4.25V, the cycle temperature is 45℃, the first cycle is 0.05C, and the second cycle starts according to different rate requirements, and the battery's rate discharge capacity and capacity retention rate are evaluated. The results of the above tests are shown in Table 1.
[0091] Table 1
[0092]
[0093]
[0094] From the test data in Table 1, it can be seen that the electronic conductivity of the unmodified sulfide electrolyte Li6PS5Cl in the control group is poor, and the capacity retention rate after multiple discharge cycles is low, while the electronic conductivity of the electron-ion mixed conductor solid electrolyte material in Examples 1-5 has been significantly improved, and the 0.3C and 2C discharge specific capacities and the capacity retention rate after 2C discharge for 300 cycles have been improved to varying degrees, indicating that the prepared battery has good rate performance and high cycle stability. Although the ionic conductivity of the electron-ion mixed conductor solid electrolyte material in Examples 1-5 has decreased to a certain extent, it does not affect the performance when used as a positive electrode electrolyte material.
[0095] In Comparative Example 1, the electronic conductivity of the electronic-ion mixed conductor solid electrolyte material prepared using ZIF-8 was not significantly improved compared with the control group, and the ion conductivity decreased to a certain extent. In Comparative Example 2, the electronic conductivity of the electronic-ion mixed conductor solid electrolyte material prepared using graphene material was significantly improved compared with the control group, but the ion conductivity decreased significantly, and the battery short-circuited after 300 cycles of 2C discharge, indicating that the prepared battery had poor rate performance and low cycle stability.
[0096] The beneficial effects of the electron-ion conductor sulfide solid electrolyte material and the preparation method thereof provided in this application include but are not limited to the following:
[0097] (1) The electron-ion mixed conductor solid electrolyte material provided by the present invention utilizes a metal organic framework material as a carrier of a sulfide solid electrolyte, and forms a mixed ion-electron conductive structure by compounding with a sulfide solid electrolyte, and is fully mixed with the positive electrode active material, which is beneficial to reducing the interface contact loss between the materials. Secondly, the metal organic framework material itself can provide sufficient electronic conductive channels, and the sulfide electrolyte therein can ensure that the ionic conductivity of the composite positive electrode is not affected. Therefore, the metal organic framework material can play the role of a conductive agent in the composite positive electrode, thereby reducing the amount of conductive agent used in the composite positive electrode, and even eliminating the need for the presence of a conductive agent, thereby achieving the goal of reducing the amount of auxiliary materials used, reducing the polarization of the battery cell, and improving the utilization rate of the positive electrode active material.
[0098] (2) The present invention limits the electronic conductivity of the metal organic framework material to greater than 10 -2 S / cm, ensuring that ions have a suitable migration path and rate in the material during use and reducing the interface impedance, thereby improving the overall conductivity of the electron-ion mixed conductor solid electrolyte material.
[0099] (3) The electron-ion mixed conductor solid electrolyte material of the present invention is equivalent to combining the conductive agent and the ion-conducting material in the traditional all-solid-state positive electrode. Since the metal organic framework material and the sulfide solid electrolyte material can be dissolved in alcohol solvents, the two materials can be mixed at the molecular level, which is beneficial to reduce the interface contact loss between the materials and reduce the internal resistance of the battery cell.
[0100] (4) The preparation method of the electron-ion mixed conductor solid electrolyte material of the present invention enhances the interface interaction between the metal organic framework material and the sulfide solid electrolyte by controlling the calcination temperature, and controls the metal organic framework material to undergo a phase transition from a metal organic framework structure to a more stable metal oxide structure, which is beneficial to improving the overall performance of the electron-ion mixed conductor solid electrolyte material.
[0101] In summary, after reading the contents of this application, those skilled in the art will appreciate that the aforementioned application contents may be presented only in an exemplary manner and may not be restrictive. Although not explicitly stated herein, those skilled in the art will appreciate that this application is intended to encompass various reasonable changes, improvements and modifications to the embodiments. These changes, improvements and modifications are within the spirit and scope of the exemplary embodiments of this application.
Claims
1. An electron-ion mixed conductor solid electrolyte material, characterized in that: The electron-ion mixed conductor solid electrolyte material is composited by embedding a sulfide solid electrolyte into a metal organic framework material as a framework, and the electronic conductivity of the metal organic framework material is greater than 10 -2 S / cm.
2. The electron-ion mixed conductor solid electrolyte material according to claim 1, characterized in that: The mixing mass ratio of the metal organic framework material and the sulfide solid electrolyte is 1:2-1:
20.
3. The electron-ion mixed conductor solid electrolyte material according to claim 2, characterized in that: The sulfide solid electrolyte includes at least Li 7-a PS 6-a X a (where X is a halogen element, 0≤a≤2), Li2S-P2S5, Li2S-P2S5-LIX (where X is a halogen element), Li2S-P2S5-Li2O, Li2S-P2S5-P2O5, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers, and Z is one of Ge, Zn or Ga), Li2S-SiS2-Li p MO q (wherein p and q are positive numbers, and M is one of P, Si, Ge, B, Al, Ga or In), one of Li2S-GeS2, Li2S-SiS2-Li3PO4.
4. The electron-ion mixed conductor solid electrolyte material according to claim 1, characterized in that: The metal organic framework material includes at least one of Cu-BHT, Co-BHT, Cu-HAB, Co-HAB, Cu-CAT, M2(TTFTB) (M is one of Mn, Co, Zn or Cd), ZnCo-ZIF, Cu-HHTQ, Cu-BTC, and Ni3(HITP)2.
5. The method for preparing the electron-ion mixed conductor solid electrolyte material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: Weigh the sulfide solid electrolyte and the metal organic framework material according to a proportion, add them into an alcohol solvent and stir them evenly to obtain material 1; Step 2: subjecting material 1 to a rotary drying process to remove the alcohol solvent, thereby obtaining material 2; Step 3: Calcinate material 2 to obtain an electron-ion mixed conductor solid electrolyte material.
6. The preparation method according to claim 5, characterized in that: In step 1, the alcohol solvent includes at least one of ethanol, methanol, isopropanol, benzyl alcohol, ethylene glycol, glycerol, butanol, and cyclohexanol.
7. The preparation method according to claim 5, characterized in that: In the step 1, the stirring speed is 450-500 rpm, and the stirring time is 8-12 h.
8. The preparation method according to claim 5, characterized in that: In the step 3, the calcination temperature is 100-300° C., and the calcination time is 1-10 h.
9. An all-solid-state battery, characterized in that: The all-solid-state battery comprises a positive electrode layer, wherein the positive electrode layer comprises the electron-ion conductor solid electrolyte material according to any one of claims 1 to 4 or the electron-ion mixed conductor solid electrolyte material prepared by the preparation method according to any one of claims 5 to 8.
Citation Information
Cited By
Solid-state battery monomer and preparation method thereof, battery device, power utilization device and energy storage device
CN122118106A
Solid-state battery cell and method of manufacturing the same, battery device, power consuming device, and energy storage device
CN122118106B